Acute type A aortic dissection: characteristics and outcomes comparing patients with bicuspid versus tricuspid aortic valve - Etz, Christian D.; von Aspern, Konstantin; Hoyer, Alexandro; Girrbach, Felix F.; Leontyev, Sergey; Bakhtiary, Farhad; Misfeld, Martin; Mohr, Friedrich W. (European journal of cardio-thoracic surgery, 2015)
OBJECTIVES The aim of this study is to investigate the clinical characteristics and postoperative outcome of patients with a bicuspid aortic valve (BAV) suffering acute dissection in comparison with their tricuspid peers. METHODS Between 1995 and 2011, 460 consecutive patients underwent emergency repair for acute type A aortic dissection. In 379 patients without connective tissue disease, the aortic valve morphology could clearly be specified (91.6% tricuspid and 8.4% bicuspid). RESULTS At the time of dissection, patients with a bicuspid valve were younger (46.7 ± 13 vs 61.6 ± 12 years, P < 0.001) with the entry tear more often located in the root compared with those with a tricuspid valve (bicuspid: 31.3% vs tricuspid: 6.3%, P < 0.001). Consequently, surgical repair warranted root replacement in 93.8% of bicuspid vs 28.8% of tricuspid valve patients (P < 0.001). The leading pathology was medial necrosis/degeneration in bicuspid and atherosclerosis in tricuspid patients (P = 0.166). Hospital mortality was 20.3% and not significantly different between the two valve morphologies, even despite the younger age of bicuspid patients: 28.1% among bicuspids vs 19.6% among tricuspids (P = 0.255). Survival after discharge was 63.3% at 10 years for all patients. BAV patients had a significantly better survival with 100% at 10 years compared with 60.2% in tricuspid valve patients (P = 0.011). Mean follow-up among survivors was comparable for bicuspid and tricuspid patients (3.7 and 4.1 years, respectively). CONCLUSIONS Patients with BAV have a distinctive dissection pattern with the entry tear frequently located in the aortic root and—despite their younger age—are subject to substantial hospital mortality. For bicuspid patients suffering from dissection, composite root replacement yields an excellent outcome equal to an age- and gender-matched normal population.